Inhibitory Effect of Ethanol Extract of Cherry Mistletoe Leaves (Dendrophthoe pentandra (L.) Miq) on Xanthine Oxidase Enzyme - Hana Daini Sabathania; Subandrate Subandrate; Sadakata Sinulingga; Safyudin Safyudin; Liniyanti D Oswari; Fatmawati Fatmawati (Sanata Dharma University, 2025)
One plant that can be used as an alternative treatment for hyperuricemia is the cherry plant. The usefulness of these plants is due to the secondary metabolite compounds that can inhibit the enzyme xanthine oxidase. Cherry mistletoe is thought to have the same flavonoids, saponins, alkaloids, terpenoids, and tannins as the cherry plant, which can act as inhibitors. The aim of the study was to determine the inhibitory effect of an ethanol extract of cherry mistletoe leaves on the xanthine oxidase enzyme. This study was conducted as an in vitro experimental study. Cherry mistletoe leaves were extracted with 96% ethanol. The extract was done with phytochemical screening, followed by an inhibition test on the xanthine oxidase enzyme using a spectrophotometer at a wavelength of 400 nm. Allopurinol was a positive control. The ethanol extract of cherry mistletoe leaves contains flavonoids, saponins, alkaloids, terpenoids, and tannins. The IC50 value of the ethanol extract of cherry mistletoe leaves was 23.44 mg/L. The ethanol extract of cherry mistletoe leaves has an inhibitory effect on the xanthine oxidase enzyme with moderate activity. Accordingly, the cherry mistletoe leaf extract can be considered as an alternative inhibitor of the xanthine oxidase enzyme in the control of hyperuricemia.